2017
DOI: 10.1111/jocn.13422
|View full text |Cite
|
Sign up to set email alerts
|

Constipation is casting a shadow over everyday life – a systematic review on older people's experience of living with constipation

Abstract: Healthcare professionals need to be aware of the experiences of living with constipation as well as the range of strategies used by patients to prevent and treat constipation. The patient perspective on constipation needs to be integrated in the strategies and actions carried out by healthcare professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…In the general population of Europe, the mean value of the reported constipation prevalence is 17.1%, and its higher value is frequently associated with older age, female sex, less self-reported physical activity, and certain medications 1 , 2 . In general population, constipation is associated not only with worse health-related quality of life (HRQoL) 3 , 4 but also with higher risk of cardiovascular events and all-cause mortality 5 - 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In the general population of Europe, the mean value of the reported constipation prevalence is 17.1%, and its higher value is frequently associated with older age, female sex, less self-reported physical activity, and certain medications 1 , 2 . In general population, constipation is associated not only with worse health-related quality of life (HRQoL) 3 , 4 but also with higher risk of cardiovascular events and all-cause mortality 5 - 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence regarding the impact of constipation on patients is inconsistent and lacking within specialist palliative care. While a systematic review of four papers on older people’s experiences suggests physical, psychological and social impact, 11 data from an Australian Palliative Care database suggests that most palliative care patients were not unduly distressed by constipation. 12 Furthermore, underestimation of symptom intensity by healthcare professionals leads to increased risk of inadequate treatment, 13 and research in chronic pain has demonstrated incongruence between the patient experience and the healthcare professional’s assessment in the perceived importance and severity of constipation.…”
Section: Introductionmentioning
confidence: 99%
“…2 While it is recognised that a co-ordinated multidisciplinary team approach may increase the survival of those with DMD and improve their quality of life (QoL) 3 adults are receiving less comprehensive and co-ordinated care compared with those in the paediatric service. 4 Aim To investigate QoL in adults with DMD living in the West of Scotland (WoS). Methods The SEIQoL-DW tool was used to assess the five most important elements that contribute to an individual's QoLthese were then used to guide qualitative interviews with six men in the WoS.…”
mentioning
confidence: 99%